2024
DOI: 10.1002/oby.24002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tirzepatide, GLP‐1 receptor agonists, and other weight loss drugs in overweight and obesity: a network meta‐analysis

Xin‐Hui Pan,
Bryan Tan,
Yip Han Chin
et al.

Abstract: ObjectiveThis network meta‐analysis evaluates the efficacy and safety of tirzepatide compared to glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA) and other weight loss drugs in the treatment of overweight and obesity.MethodsMEDLINE, Embase, and Cochrane CENTRAL were searched for randomized controlled trials on tirzepatide, GLP‐1 RA, and weight loss drugs approved by the US Food and Drug Administration. A network meta‐analysis was performed, drawing direct and indirect comparisons between treatment groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 119 publications
1
1
0
Order By: Relevance
“…Corresponding to the signal intensity for weight loss poor of GLP-1 RAs in our study, a network meta-analysis showed a decreasing trend in weight loss efficacy for tirzepatide, semaglutide, and liraglutide ( Pan et al, 2024 ). The weight loss effect produced by liraglutide in previous studies was individualized across subjects, with more significant fat mass reductions in females, and the starting point for measurement of the weight loss effect is recommended to start from baseline ( Santini et al, 2023 ; Schultes et al, 2024 ).…”
Section: Discussionsupporting
confidence: 69%
“…Corresponding to the signal intensity for weight loss poor of GLP-1 RAs in our study, a network meta-analysis showed a decreasing trend in weight loss efficacy for tirzepatide, semaglutide, and liraglutide ( Pan et al, 2024 ). The weight loss effect produced by liraglutide in previous studies was individualized across subjects, with more significant fat mass reductions in females, and the starting point for measurement of the weight loss effect is recommended to start from baseline ( Santini et al, 2023 ; Schultes et al, 2024 ).…”
Section: Discussionsupporting
confidence: 69%
“…Despite dire forecast trends of metabolic diseases raising concerns of a potential second wave of metabolic-related CVD progression, there is a sense of optimism with the emerging role of novel cardioprotective agents including sodium-glucose cotransporter-2 inhibitors 35 and glucagon-like peptide-1 receptor agonists, 36 that target the reduction of the overall dysmetabolic milieu rather than just CVD in isolation. 37 , 38 Urgent action including research and information exchange is needed to ensure equitable access of lower-income countries to these powerful but expensive medical innovations across Asia.…”
Section: Discussionmentioning
confidence: 99%